Marangoni convection in a relatively hotter or cooler liquid layer with free boundaries - Gupta, Anil K.; Shandil, R.G. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we study the onset of cellular convection in a horizontal fluid layer heated from below, with a free-slip boundary condition at the bottom when the driving mechanism is surface tension at the upper free surface, in the light of the modified analysis of Banerjee et al. (Jour. Math. & Phys. Sci., 1983, 17, 603).
Keywords: Surface tension; convection; conducting; linear stability